2007
DOI: 10.1634/stemcells.2006-0616
|View full text |Cite
|
Sign up to set email alerts
|

Baculoviral Vector-Mediated Transient and Stable Transgene Expression in Human Embryonic Stem Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 19 publications
2
98
0
2
Order By: Relevance
“…These observations contradicted with previous data reporting that the transgene cassette flanked by the ITR elements, with or without the rep gene, offered sustained expression in the rat brains (490 days), 24 in human neuronal cells 29 and in human embryonic stem cells (422 weeks). 30 The disparity probably arose from the differences in the intrinsic properties (for example, repertoire of cellular factors) or in the proliferation rates of the cell types. Should integration not occur efficiently, the ITR-flanking cassette was more likely to persist in the slow proliferating neuronal/stem cells for a longer period of time than in the rapidly proliferating HEK293 cells in which the transgene was diluted out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations contradicted with previous data reporting that the transgene cassette flanked by the ITR elements, with or without the rep gene, offered sustained expression in the rat brains (490 days), 24 in human neuronal cells 29 and in human embryonic stem cells (422 weeks). 30 The disparity probably arose from the differences in the intrinsic properties (for example, repertoire of cellular factors) or in the proliferation rates of the cell types. Should integration not occur efficiently, the ITR-flanking cassette was more likely to persist in the slow proliferating neuronal/stem cells for a longer period of time than in the rapidly proliferating HEK293 cells in which the transgene was diluted out.…”
Section: Discussionmentioning
confidence: 99%
“…The WPRE (woodchuck hepatitis virus post-transcriptional regulatory element), a cis-acting element that enhanced the baculovirus-mediated transgene expression in vertebrate cells, 46 was amplified from pFastBac1-CMV-EGFP-WPRE 30 (kindly provided by Professor Shu Wang of National University of Singapore) and inserted into pBac-hEA between the hEA gene and pA to yield pBac-hEA/w. The IR/ DR elements from pT2-BH were digested by SalI/NotI and cloned into pFastBacDpolhDp10 to yield pBac-T2.…”
Section: Preparation Of Recombinant Baculovirusesmentioning
confidence: 99%
“…This insect virus is emerging as a potentially safe class of gene delivery vectors because of its inability to replicate or cause toxicity in mammalian cells. [19][20][21][22][23] Baculovirus-derived vectors are capable of transducing both dividing and non-dividing cells including human embryonic stem cells (hESCs) 24,25 and mesenchymal stem cells. 26,27 The great potential of NSCs in cancer therapy highlights the need for consistent and renewable sources for the collection or production of uniform human NSCs suitable for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Baculovirus vectors are able to transduce a wide range of human cell lines, including primary cells such as bone marrow fibroblasts, neural cells, hepatocytes and mesenchymal stem cells. Zeng and coworkers (Zeng et al, 2007) have demonstrated their ability to transduce human embryonic stem cells without altering their characteristics. The hybrid vectors contained three promoters, one driving the expression of the complete baculovirus genome, the second expressing eGFP and the third (AAVp5) driving the expression of Rep78.…”
Section: Baculovirus/aavmentioning
confidence: 99%